Obesity and pregnancy: possible ways to overcome complications and improve reproductive outcomes - Irina A. Lapina; Yulia Е. Dobrokhotova; Vladislav V. Taranov; Yury A. Sorokin; Tatiana G. Chirvon; Anastasiya A. Malakhova (IP Berlin A.V., 2023)
Introduction. Obesity, due to its high prevalence and relevance, can be considered an epidemic of modern society. Obesity-related microcirculatory vascular disease and chronic inflammation with endothelial dysfunction are associated with adverse effects on reproductive potential. Sulodexide reduces the risk of hemostatic complications in patients planning pregnancy due to its polypotent effect, which is especially important in metabolic disorders and comorbidities. Therefore, it is promising to assess the effectiveness of integrated management of obese patients as part of pregnancy planning. Aim. To modify the complex treatment of obesity in patients planning pregnancy to reduce the risk of reproductive losses and gestational complications. Materials and methods. The prospective analysis included 92 patients with grade 1 obesity. According to the clinical protocols and guidelines of the Reproductive Health Professional Medical Association, 46 patients in the control group (group 1) were prescribed treatment to reduce the body mass index, including lifestyle correction, folic acid, and vitamin D. Patients in the comparison group (Group 2, n=46) also received endotheliotropic agent sulodexide. The treatment efficacy was analyzed based on the frequency of pregnancy, the change of laboratory markers of endothelial dysfunction, the incidence of gestational complications, and reproductive losses. Results. The study showed that in comparison group patients, the frequency of pregnancy (58.7% of cases in Group 1, 71.7% in Group 1), favorable course of the first trimester (39.1% in Group 1, 63.0% in Group 2), and delivery at term (30.4% in Group 1, 56.5% in Group 2) were higher compared to the control group. There was also a more significant decrease in the body mass index and endothelial dysfunction factors (homocysteine level in group 1 before treatment was 172.4 mol/L, and 141.8 mol/L after treatment; 191.7 mol/L before treatment and 91.4 mol/L after treatment in Group 2, respectively) in patients receiving complex treatment with sulodexide. Analysis of the pregnancy course showed a lower risk of gestational diabetes (33.3% in Group 1 and 13.8% in Group 2). Conclusion. Treatment of obesity in patients planning pregnancy requires a complex effect aimed at correcting lifestyle, reducing body weight, restoring the endothelial layer, and reducing the severity of chronic inflammation, thus improving reproductive outcomes and minimizing the risk of gestational complications.